2016
DOI: 10.1002/maco.201608863
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy‐coated reinforcement in concrete structures: Results of a Swiss pilot project after 24 years of field exposure

Abstract: Reinforced concrete is the most common construction material of civil infrastructure. In severe environment, e.g., chloride exposure, concrete deterioration can occur with consequences on the durability of the structure. The use of epoxy‐coated reinforcement is a strategy to control chloride‐induced reinforcement corrosion, particular by prolonging the initiation and propagation phase. The epoxy‐coating acts as a physical barrier to chlorides and the electrolyte concrete. However, the effectiveness of the stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The potential of ECRCD suggested that the small damages to epoxy were not able to initiate the corrosion at the steel surface. Keßler et al (2016) suggested that the damages will only be harmful in the case where a macro-cell is formed between these damages and an uncoated rebar or other defected portion. Then these defects could act as a cathode and cause disbondment of epoxy near the damaged surface.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The potential of ECRCD suggested that the small damages to epoxy were not able to initiate the corrosion at the steel surface. Keßler et al (2016) suggested that the damages will only be harmful in the case where a macro-cell is formed between these damages and an uncoated rebar or other defected portion. Then these defects could act as a cathode and cause disbondment of epoxy near the damaged surface.…”
Section: Resultsmentioning
confidence: 99%
“…The salt spraying on highways to melt the snow caused corrosion problems in the bridges in North America and other countries with cold climate. To overcome this problem, a research was initiated by the National Institute of Standards in the USA, in the early 1970s, which resulted in epoxy-coated reinforcing bars (Manning, 1996; Keßler et al , 2016). The optimum thickness required for corrosion protection, bond strength, and creep requirement was established to be 0.18 ± 0.05 millimeter (mm) (Manning, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations